2015
DOI: 10.14295/2238-6416.v70i6.454
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Das Caracteristicas Fisico-Químicas, Microbiológicas E Rotulagem De Leite Pasteurizado Comercializado Na Microrregião De Ubá – Minas Gerais

Abstract: RESUMOObjetivou-se avaliar as características físico-químicas, microbiológicas e a rotulagem de sete marcas de leite pasteurizado comercializados na microrregião de Ubá -Minas Gerais. Foram realizadas análises físico-químicas de acidez, lactose, gordura, proteína, EST, ESD, pH, densidade, ponto crioscópico, umidade e cocção, bem como análises microbiológicas de coliformes totais e termotolerantes e contagem padrão em placas. Para as análises físico-quimicas, foram obtidos os seguintes resultados médios: 16ºD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A wine with a dry extract above 30 g L − 1 is classified as a well-bodied beverage (Castilhos & Del Biachi, 2011). In addition, the amounts of sugar added to the musts during alcoholic fermentation for chaptalization and before bottling, increased the dry extract content of the product (Boeira et al, 2020;Oliveira, Souza & Mamede, 2011). Thus the results obtained here indicated that the passion fruit fermented alcoholic beverage were very well bodied.…”
Section: Physicochemical Composition Of the Passion Fruit Fermented A...mentioning
confidence: 55%
“…A wine with a dry extract above 30 g L − 1 is classified as a well-bodied beverage (Castilhos & Del Biachi, 2011). In addition, the amounts of sugar added to the musts during alcoholic fermentation for chaptalization and before bottling, increased the dry extract content of the product (Boeira et al, 2020;Oliveira, Souza & Mamede, 2011). Thus the results obtained here indicated that the passion fruit fermented alcoholic beverage were very well bodied.…”
Section: Physicochemical Composition Of the Passion Fruit Fermented A...mentioning
confidence: 55%
“…Several techniques and procedures can be employed for the quality control of dairy products, one of which is colorimetric analysis with the help of a colorimeter, using reagents and standards (Kalinin et al, 2013). According to Oliveira et al (2011) the use of colorimeters has been frequently employed to verify the color of different beverages, such as wine and soluble coffee, juices, and products. Although the classical analysis for the evaluation of the parameter color in dairy products uses commercial colorimeters, its high cost and the need for reagents become the main disadvantages of the employment of this technique (Kalinin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%